Notes From An Odin Actress : Stones of Water. - Varley, Julia (Taylor & Francis, 2010)
The author has been a member of Odin Theatret for 33 years. This title offers a personal account of her work with Eugenio Barba and this world-renowned theatre company. It describes her experience of being an actress from a professional and female perspective.